2012
DOI: 10.1143/jpsj.81.114712
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Perturbation Theory for Antiferromagnetic Heisenberg Spin Chains

Abstract: A recently developed numerical method, entanglement perturbation theory (EPT), is used to study the antiferromagnetic Heisenberg spin chains with z-axis anisotropy λ and magnetic field B. To demonstrate the accuracy, we first apply EPT to the isotropic spin-1 2 antiferromagnetic Heisenberg model, and find that EPT successfully reproduces the exact Bethe Ansatz results for the ground state energy, the local magnetization, and the spin correlation functions (Bethe ansatz result is available for the first 7 latti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…In exact agreement with Bethe ansatz GS energy [31], this allows for precise computation of spin-spin correlations for separations over 10000 sites. The correlations reproduced results in ref [32], both of which agree with the prediction by the conformal field theory [33] that there is a loga- rithmic correction multiplicative to the power-law decay predicted by the bosonization theory [34]. As Fig.…”
supporting
confidence: 87%
“…In exact agreement with Bethe ansatz GS energy [31], this allows for precise computation of spin-spin correlations for separations over 10000 sites. The correlations reproduced results in ref [32], both of which agree with the prediction by the conformal field theory [33] that there is a loga- rithmic correction multiplicative to the power-law decay predicted by the bosonization theory [34]. As Fig.…”
supporting
confidence: 87%
“…6b, which shows that the single CSF results mimic the exact result even for large lattice sizes. However, the shortrange behavior of the exact spin-spin correlation function follows a power law decay [39], Ŝz Using the method of generating functions, Sato et al [163] found the exact thermodynamic limit results for S z 1 • S z r up to r = 7, which are shown in Table III along [164], derived a relation of A(r) = −0.1473r −0.9604 with an error of 0.1% for the odd separations, which also fits the even sites with an opposite sign. Based on a bosonization approach, Hikihara and Furusaki [165] find a critial exponent b = −1.…”
Section: Spin-spin Correlation Functionsmentioning
confidence: 99%
“…For instance, DMRG works extremely well in 1D but not in 2D. When dealing with a 2D lattice, the wave function obtained in DMRG has a matrix product state (MPS) [22,[38][39][40][41][42][43][44][45][46] form that is built on a winded 1D lattice which resembles the 2D lattice [15,36]. See Fig.2(b) for an illustration.…”
Section: A Problem Descriptionmentioning
confidence: 99%